Trade Dependency, Bargaining and External Debt. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper analyzes the factors determining the payment on outstanding debt in the presence of partial defaults, and the feasibility of renewed investment. We show that a higher relative size of sectors with lower substitutability between domestic and foreign products will increase the resource transfer ceiling. Even with a partial default, investment in highly trade dependent sectors with high productivity may be warranted. This investment can be implemented by a marginal relief of the present debt service, in exchange for investment in the proper sector. A way to partially overcome some of the monitoring problems associated with renewed investment is through direct investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: External Finance; Trade Dependency; WP